PENGARUH KONSENTRASI FULI PALA TERHADAP DAYA TANGKAP LALAT BUAH ( Bactrocera sp) DI KEBUN BUAH KABUPATEN HALMAHERA UTARA - Sunarno Sunarno; Martha Ruruk (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
A study about effect of fuli nutmeg concentration on fruit flies (Bactrocera sp) trapping in orchards in North Halmahera Regency had been conducted on January 2016. This study aimed at analysing effect of difference fuli nutmeg concentration on fruit flies (Bactrocera sp) trapping ability and knowing the best effective time of trapping the fruit flies (Bactrocera sp). This study used group random sampling design with five different concentrations i.e., P0, P1, P2, P3, P4 and P5 within five repetitions. This study was started by producing fuli nutmeg extract. Designing the trap was done after produced fuli nutmeg extract. Next steps were setting the trap and analysing data. Data were analysed by using difference mean analysis with 5% of level acceptance. This research showed that there was no fruit flies had successfully trapped on sample with concentration of 0 ml of fuli nutmeg extract (P0). There were 100.8 fruit flies successfully trapped on sample of 2 ml fuli nutmeg extract (P4). These were the largest number than other. In average, there were 125 fruit flies had successfully trapped in the afternoon and 98.4 fruit flies in the morning. In afternoon was the best time for trapping fruit flies than in the morning.